2020
DOI: 10.1186/s42523-020-00046-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-induced alterations and repopulation dynamics of yellowtail kingfish microbiota

Abstract: Background: The use of antibiotics in aquaculture is a common infection treatment and is increasing in some sectors and jurisdictions. While antibiotic treatment can negatively shift gut bacterial communities, recovery and examination of these communities in fish of commercial importance is not well documented. Examining the impacts of antibiotics on farmed fish microbiota is fundamental for improving our understanding and management of healthy farmed fish. This work assessed yellowtail kingfish (Seriola lalan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 103 publications
1
24
0
Order By: Relevance
“… 2020 ; Legrand et al . 2020c ). In this study, we first investigated whether the microbial communities of digesta samples were different to those associated with mucosal samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2020 ; Legrand et al . 2020c ). In this study, we first investigated whether the microbial communities of digesta samples were different to those associated with mucosal samples.…”
Section: Discussionmentioning
confidence: 99%
“…The exposed mucosa was then collected using a sterile glass microscope slide as described previously (Legrand et al . 2020c ) and placed in a 50‐ml falcon tube. Gloves were used and changed between the collection of each sample type to avoid contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasma was the most dominant genus in the spleens of healthy fish, the third most dominant in the spleens of diseased fish, much less abundant in the intestine of diseased fish and nearly negligible in the intestine of healthy fish (Table 2 ). According to Legrand et al [ 40 ], Mycoplasma was identified in the intestines of a variety of fish species but not always with association to disease. Bozzy et al [ 19 ], who studied the intestinal microbiota of healthy and diseased Atlantic salmon, reported that Mycoplasma was more dominant in healthy fish compared to the diseased fish.…”
Section: Discussionmentioning
confidence: 99%
“…were shown to perturb their gut microbiomes and lead to states of dysbiosis, with increased abundances of opportunistic pathogens (Kim et al, 2019;Legrand et al, 2020). Carlson et al (2017) showed that 1 week of exposure to an antibiotic caused significant perturbation of the gut mucosal microbiome in mosquitofish (Gambusia affinis), and 1 week of recovery was not sufficient to return the community to the undisturbed state.…”
Section: Introductionmentioning
confidence: 99%